Effectiveness and Limitations of Core Needle Biopsy in the Diagnosis of Thyroid Nodules: Review of Current Literature - Jung Hyun Yoon; Eun-Kyung Kim; Jin Young Kwak; Hee Jung Moon (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
Fine needle aspiration (FNA) is currently accepted as an easy, safe, and reliable tool for the diagnosis of thyroid nodules. Nonetheless, a proportion of FNA samples are categorized into non-diagnostic or indeterminate cytology, which frustrates both the clinician and patient. To overcome this limitation of FNA, core needle biopsy (CNB) of the thyroid has been proposed as an additional diagnostic method for more accurate and decisive diagnosis for thyroid nodules of concern. In this review, we focus on the effectiveness and limitations of CNB, and what factors should be considered when CNB is utilized in the diagnosis of thyroid nodules.